Intelligent methods for optimization design of lightweight fiber-reinforced composite structures: A review and the-state-of-the-art - Chen, Yonglin; Zhang, Junming; Li, Zefu; Zhang, Huliang; Chen, Jiping; Yang, Weidong; Yu, Tao; Liu, Weiping; Li, Yan (Frontiers in Materials, 2023)
As the application of lightweight fiber-reinforced composite structures reaches an unprecedented scale in industry, design technology for composite structures becomes crucial for enhancing performance, improving productivity, and reducing cost. In recent years, the rapid development of intelligent technology, such as big data, deep learning, and machine learning, has promoted the development of design technology. However, the current situation and intellectualization of the design technology is not well summarized. This paper reviews the advance in design technologies for fiber-reinforced composite structures, including prediction and optimization methods for composite properties. Then, their intellectualization development is overviewed. Finally, the development trend of intelligent design technologies and intelligent composite structures are discussed. This work can provide a reference for researchers in the related field.